The Effect of stunting on number of primary teeth eruption among 19-60 months old stunted toddlers in Panduman Village, Jelbuk, East Java - Dwi Prijatmoko; Sulistyani; Rezza D. Ardhita (DiscoverSys Inc., 2022)
Objective: The aim of this study was to determine the effect of growth stunting on the number of primary teeth eruption from a representative Panduman Village, Jelbuk, East Java. Material and Methods: This is an analytic observational with a cross sectional approach study. Parents of the stunted toddlers were invited and 25 toddlers (age between 19-60 months) were participated in the study. There were 25 normal growth toddlers who had the same age range who were also invited in this study as for the normal control group. In this study, the tooth were considered to have erupted if the crown if the tooth was clinically visible through the gingival mucosa. Data was than devided into 4 (20-30, 31-40, 41-50 and 51-60) age categories, The average data for each category was analyzed with independent T test if necesary. Results: All primary incisors have been erupted for all age category for both stunted and normal control population. The number of primary canines were significantly difference (P> 0.02) only in the 20-30 months age cateory. It may sugest that stunting affect the eruption time of primary canines. However, the number of erupted primary molars were not significantly difference in all age categories between stunted and normal controls groups. Conclusion: Stunting potentially affect the eruption time of primary teeth. Further study involving larger number of sampel is required to conform this findings.